2017
DOI: 10.20950/1678-2305.2017v43n3p399
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de alevinos de tilápia em sistema de bioflocos sob diferentes relações carbono/nitrogênio

Abstract: RESUMONa presente pesquisa, avaliou-se o efeito da relação carbono/nitrogênio (C:N), na qualidade da água, produtividade e composição centesimal dos alevinos de Oreochromis niloticus durante 58 dias de cultivo. O desenho experimental consistiu em quatro tratamentos: um sistema convencional (controle) e três sistemas de biofloco (CN10, CN15 e CN20). Foram utilizadas 12 unidades experimentais de 0,04 m 3 , com 30 peixes (750 peixes m -3 ) com peso médio individual de 1,55±0,01 g. Verificou-se a existência de int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
5
5
0
Order By: Relevance
“…The final weight and length, FCR, SGR, PER and yield were higher in BFT-30 and BFT-C30 as compared than BFT-50 and BFT-C50. Pérez-Fuentes et al (2016), Zapata-Lovera et al (2017 and Liu et al (2018) observed a higher zootechnical performance of Nile tilapia fingerlings in C/N (10:1) ratios compared with higher C/N (20:1) ratios, as in the present study, where treatments with 50% addition of molasses presented lower final weight at the end of the cultivation. It is probable that the lower levels of solids (Pérez-Fuentes et al, 2016) and the dominance of the mix of microalgae, heterotrophic bacteria and autotrophic bacteria is more beneficial for fish and shrimp growth (Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The final weight and length, FCR, SGR, PER and yield were higher in BFT-30 and BFT-C30 as compared than BFT-50 and BFT-C50. Pérez-Fuentes et al (2016), Zapata-Lovera et al (2017 and Liu et al (2018) observed a higher zootechnical performance of Nile tilapia fingerlings in C/N (10:1) ratios compared with higher C/N (20:1) ratios, as in the present study, where treatments with 50% addition of molasses presented lower final weight at the end of the cultivation. It is probable that the lower levels of solids (Pérez-Fuentes et al, 2016) and the dominance of the mix of microalgae, heterotrophic bacteria and autotrophic bacteria is more beneficial for fish and shrimp growth (Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Some authors reported successfully culturing Nile tilapia in BFT (Long et al, 2015;Miranda-Baeza et al, 2017;Zapata-Lovera et al, 2017), including a study in brackish water (8 g L -1 ) (Brol et al, 2017;Lima et al, 2018). However, due to the high stocking densities and minimal water exchange, nutrients accumulate, mainly nitrogen and phosphorus, in the biofloc culture (Krummenauer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These processes and consumptions explain the variation and decrease in total alkalinity in T1 treatment in both stages, affecting the buffering capacity of water (Baldisserotto, 2013), with a response to this process being the lower pH, total ammonia nitrogen (TAN), nitrite, settleable solids (SS) and the higher concentration of nitrate, with differences regarding T2 and T3 treatments. Similar processes and conditions were reported by Zapata et al (2017) for the culture of O. niloticus juveniles in biofloc at three C/N ratios (10, 15 and 20/1), where the lowest concentrations of total alkalinity, pH, SS, nitrite and the highest NO 3 were found in the C/N ratio 10/1 followed by the ratio 15/1. During larvae and fry culture experiments, the mean values of total ammonia nitrogen (TAN) in this study were similar to the lethal concentration of 50% (LC50) of TAN reported for pacu (Piaractus mesopotamicus) by Barbieri and Vigliar Bondioli (2013), where juveniles (1.2 ± 0.3 g) exposed for 96 hours at pH of 6.98 (6.78-7.15) and temperature of 25°C presented an LC50 of 1.97 (1.43-2.72) mg/L.…”
Section: Discussionsupporting
confidence: 83%
“…However, Zapata et al (2017) reported a better growth performance in the rearing of tilapia juvenile (Oreochromis niloticus) at a C/N ratio of 10/1, reducing production costs by decreasing the input of organic carbon and oxygen consumption (Xu et al, 2016), being this ratio the one reported by different authors in the culture of species in biofloc system (Crab et al, 2010;Green & McEntire, 2017;Kumar et al, 2015;Suita et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Meanwhile, biofloc systems have become consolidated in aquiculture because of their good productive results, for Oreochromis niloticus for example (Wambach, 2013;Zapata-Lovera et al, 2017;Bosisio et al, 2017;Lima et al, 2018). This is due to the equilibrated microbial community in biofloc systems and their need for low water exchange, which helps reduce the release of effluents into the environment and avoid the introduction of pathogens (Azim and Little, 2008;Luo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%